SALAFI, MEDIA BARU DAN MORAL PANIC STUDI ATAS MAJLIS AL-KHIDHIR - Shinta Nurani (IAIN Manado, 2019)
Abstract: This paper is a case study of Majlis al-Khidhir, one of the Salafi Group in Indonesia which experienced moral panic as its existence might be eroded by modernity along with the changes of da'wah media. The existence of many Salafy groups massively utilizing internet media for their da’wah and propaganda in fact have damaged the image of Salafi da’wah. In this case, Majlis al-Khidhir, finally, do negotiations by maintaining its literalist ideology, at the same time open to new internet media to spread its dakwah activities. As a result, 'telegram' became the most effective new medium for Majlis al-Khidhir to circulate a fatwa and interact with its loyal followers.Keywords: New Media, Moral Panic, Salafi, Majlis al-Khidhir Abstrak: Tulisan ini merupakan studi kasus Majlis al-Khidhir, salah satu kelompok Salafi di Indonesia yang mengalami moral panic karena khawatir eksistensinya akan tergerus oleh modernitas dengan adanya perubahan media dakwah. Selain itu, keberadaan kelompok yang mengatasnamakan dakwah Salafi (Salafi Selebriti) padahal sejatinya merusak citra dakwah Salafi telah bergerak lebih cepat dalam memanfaatkan media dakwah tersebut. Akhirnya negosiasi terhadap modernitas dilakukan Majlis al-Khidhir dengan tetap memegang teguh ideologi literalisnya tetapi terbuka terhadap media baru untuk melebarkan dakwahnya. Konsekuensinya, ‘telegram’ menjadi media baru paling efektif bagi Majlis al-Khidhir untuk mengeluarkan fatwa dan berinteraksi dengan pengikut setianya.Kata Kunci: Media Baru, Moral Panic, Salafi, Majlis al-Khidhir.